INFLUENCE OF DIGITAL TECHNOLOGIES ON THE DEVELOPMENT OF SOME ASPECTS OF THE THEORY OF CONSTITUTIONAL REGULATION OF RELATIONS IN THE REPUBLIC OF KAZAKHSTAN: PROBLEMS AND WAYS FOR IMPROVEMENT - Nurmagambetov , Рашит Габитович; Ukin, Сымбат Кенжебекович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
In the article, the author, by analyzing various points of view, proposes theoretical and practical ways to improve such a complex phenomenon of constitutional and legal reality as constitutional regulation of social relations. Considering the dynamics of the development of digitalization products and the deepening of this process, as well as its impact on constitutional matter, the lack of unified universal criteria, the author considers it necessary to invite deputies of the Senate and Mazhilis of the Parliament of the Republic of Kazakhstan, judges of the Constitutional Court of the Republic of Kazakhstan, representatives of executive authorities, scientists to begin work on the popularization of constitutional terms reflecting the influence digitalization, initiate systematic work to include such a comprehensive document as the “Concept of constitutional regulation of the Republic of Kazakhstan”. According to the author, in addition to terms, it should also include a set of practical actions, in particular conducting constitutional monitoring, adding effective constitutional instruments such as constitutional incentives and constitutional permissions, etc. In practical terms, the concept of the development of constitutional regulation will allow us to formulate a holistic view of the directions of regulation of social relations, determine the areas of constitutional regulation, and the role of state bodies in this process. Specifying the goals, objectives, and stages of the sequence of measures that contribute to the development of constitutional regulation will ensure the improvement of constitutional regulation and will also solve several pressing problems - constitutional norms correspond to legal reality, would not allow for their arbitrary interpretation, and would establish uniform standards of behavior for subjects of legal relations. Understanding that this process will take more than one day, we note that in the opinion of the author, the state has all the necessary resources to carry out this work.